2019
DOI: 10.3390/sym11111421
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Economies: An Analysis of the Determinants of Employment in the Cities of Ecuador

Abstract: The objective of this investigation is to study the role of agglomeration economies (manufacturing) in urban employment growth, as a proxy for economic growth, between 1980 and 2010 in Ecuador. The three measures of agglomeration-specialization, diversity, and density-are tested to determine their effect on employment growth in industries. The empirical analysis is based on firm- and city-level data from manufacturing activities. A model is proposed to estimate the effect of agglomeration economies on the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
5
0
1
Order By: Relevance
“…In a complementary way, to illustrate the relationship between the number of new firms by sector and canton and the level of employment of the industry itself through Figure 3, it is possible to establish that there is a strong correlation between both of the order of 0.99, as well as a small amount of variation in the creation of new firms. Analysis for the Ecuadorian case was previously performed by Pontarollo et al [85] who verified a special heterogeneity of the cantons; as well as it was found that in the period 1980-2010, the growth of employment in the industrial sector in Ecuador responds to localization economies and not to urbanization economies [38]. Therefore, it seems that there is a clear pattern of permanence in the location of new firms with respect to the location of employment in the sector.…”
Section: The Industrial Dynamics Of Ecuadormentioning
confidence: 87%
See 3 more Smart Citations
“…In a complementary way, to illustrate the relationship between the number of new firms by sector and canton and the level of employment of the industry itself through Figure 3, it is possible to establish that there is a strong correlation between both of the order of 0.99, as well as a small amount of variation in the creation of new firms. Analysis for the Ecuadorian case was previously performed by Pontarollo et al [85] who verified a special heterogeneity of the cantons; as well as it was found that in the period 1980-2010, the growth of employment in the industrial sector in Ecuador responds to localization economies and not to urbanization economies [38]. Therefore, it seems that there is a clear pattern of permanence in the location of new firms with respect to the location of employment in the sector.…”
Section: The Industrial Dynamics Of Ecuadormentioning
confidence: 87%
“…They suggested that establishments in industries with minor knowledge spillovers, or more labor pooling, are more concentrated. Specifically, for the case of Ecuador Torres et al [38], a concentration index was calculated and they found that the economic activity tends to cluster in relatively few cities, mainly Guayaquil and Quito, those cities that since colonial times have maintained their supremacy over others and, therefore, perform important functions economic, regional, and international.…”
Section: Agglomeration Economiesmentioning
confidence: 99%
See 2 more Smart Citations
“…La falta de datos temporales impide el análisis de la evolución de las disparidades del ICR. Sin embargo, a nivel cantonal no han existido cambios significativos en la estructura económica del país las últimas décadas como lo demuestran recientemente Torres-Gutiérrez, et al (2019). En consecuencia, el ICR se constituye en un indicador de desarrollo integral de los cantones.…”
Section: Conclusionesunclassified